Optimization and Single-Stage Centrifugal Contactor Experiments with the Novel Hydrophilic Complexant PyTri-Diol for the i-SANEX Process. Issue 4 (7th June 2018) - Mossini, Eros; Macerata, Elena; Wilden, Andreas; Kaufholz, Peter; Modolo, Giuseppe; Iotti, Nicolò; Casnati, Alessandro; Geist, Andreas; Mariani, Mario
ABSTRACT: The applicability of 2, 6-bis[1-(propan-1-ol)-1, 2, 3-triazol-4-yl)]pyridine (PyTri-Diol) in the innovative Selective ActiNide EXtraction ( i -SANEX) process as water-soluble complexing agent was studied. Preliminary batch experiments were aimed at identifying the optimal formulation of the PyTri-Diol solution and at preparing the ground for single-stage centrifugal contactor experiments. A N, N, N ′, N ′ tetraoctyl diglycolamide (TODGA)-based solvent loaded using a spiked synthetic Plutonium and Uranium Reduction EXtraction raffinate and the optimized PyTri-Diol aqueous phase were contacted in a single-stage annular centrifugal contactor setup with three different flow-rate conditions. No hydrodynamic problems were encountered, and promising minor actinide separation from other cations was achieved with satisfactory kinetics and stage efficiency. The flow sheet of a TODGA–PyTri-Diol-based i -SANEX process was designed exploiting batch and single-stage data, promoting the CHON compliant PyTri-Diol as excellent alternative to the formerly used SO3 –Ph–BTP.